An Empirical View on Ethical Values and Moralism of Public Bus Service in Kuantan - Diyana, Kamarudin; Mohammad Fitri, Idrus; Siti Aisyah, Ismail; Shariman, Mustafa (KnE Social Sciences, 2019)
Ethics is a discipline dealing with a set of rules, principles, and beliefs used to judge the value of human actions. Ethics are relevant in the transportation sector because of the diversity and the social relevance of its effects, both positive and negative. Ethics in Business is nothing but the do’s (good things and honest activities) and don’ts (bad things, cheating, bribe, duplicate products) by the marketers in the business. There should be business ethics, meaning that the business should be conducted according to certain self-recognized moral standards. Most of the government agencies have very strict conduct of rules and moral standard on which the entire functioning is hovering and most of the time customer gains the benefits. In order to protect the public and company interest, the practice of professionalism in bus services should be practiced. The objective of this research is to analyse the ethical issue in Rapid Kuantan bus service. The study utilizes informal interview toward operation and bus control centre staff and observational as its methodology. Four dimension of different cases discussed in this paper to see the relation of action taken and its relation with the said elements. In this study, the expected outcome is high ethics and morality is a vital value and characteristic that lead to the trusted and effective of bus services.